1981
DOI: 10.1111/j.1469-8137.1981.tb01748.x
|View full text |Cite
|
Sign up to set email alerts
|

PRELIMINARY INVESTIGATIONS INTO THE STRUCTURE OF THE ROOTS OF THE MANGROVES, AVICENNIA MARINA AND BRUGUIERA GYMNORRHIZA, IN RELATION TO ION UPTAKE

Abstract: SUMMARYThe structure of the roots of Avicennia marina (Forsk.) Vierb., a salt excretor, and Bruguiera gymnorrhiza (L.) Lam., an excluder (non-excretor), differed in tbe lengtb and tbickness of tbe root cap, pbenolic content, tbe development of tbe Casparian strip in tbe endodermis and in the differentation of tbe vascular tissues.The uptake and distribution of lantbanum, used as a marker for ion movement differed in the two species. Tbougb botb bad similar root concentrations, tbe amount of lantbanum in tbe le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…Rhizophora mangle is not provided with salt glands, but it keeps the xylem sap essentially free of NaCl by ultrafiltration at the membranes of root cells (Scholander et al 1966;Scholander 1968). The concentration of xylem sap is about one-tenth than that of seawater (Lawton et al 1981). Furthermore, in B. gymnorrhiza, hypocotyls function as an additional filter to retain salt from the shoot (Lawton et al 1981).They maintain ionic balance through K ?…”
Section: Salt Secretion Salt Exclusion and Salt Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizophora mangle is not provided with salt glands, but it keeps the xylem sap essentially free of NaCl by ultrafiltration at the membranes of root cells (Scholander et al 1966;Scholander 1968). The concentration of xylem sap is about one-tenth than that of seawater (Lawton et al 1981). Furthermore, in B. gymnorrhiza, hypocotyls function as an additional filter to retain salt from the shoot (Lawton et al 1981).They maintain ionic balance through K ?…”
Section: Salt Secretion Salt Exclusion and Salt Accumulationmentioning
confidence: 99%
“…The concentration of xylem sap is about one-tenth than that of seawater (Lawton et al 1981). Furthermore, in B. gymnorrhiza, hypocotyls function as an additional filter to retain salt from the shoot (Lawton et al 1981).They maintain ionic balance through K ? /Na ?…”
Section: Salt Secretion Salt Exclusion and Salt Accumulationmentioning
confidence: 99%
“…As a consequence, they grow in a waterlogged soil with a more limited oxygen supply for root respiration and, in common with other mangrove species growing in anoxic soil conditions with a long inundation period, they have a special anatomical structure, the aerenchyma tissue, in their submerged roots 10,20 . Lawton et al 21 reported that root structure of the related A. marina is composed of large air spaces in the cortex.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Rhizophora mangle does not have salt glands, but it keeps the xylem sap essentially free of NaCl by ultrafiltration at the membranes of root cells [41,49]. The Na þ concentration of xylem sap is about 10% than that of sea water [50]. Furthermore, in Bruguiera gymnorrhiza, hypocotyls function as an additional filter to retain salt from the shoot [50].…”
Section: Salt Exclusion By Ultrafiltration At the Membranes Of Root Cmentioning
confidence: 99%
“…The Na þ concentration of xylem sap is about 10% than that of sea water [50]. Furthermore, in Bruguiera gymnorrhiza, hypocotyls function as an additional filter to retain salt from the shoot [50]. They maintain ionic balance through K þ / Na þ exchange at the xylem parenchyma cells in the basal part and vacuolar K þ /Na þ exchange in transpiring leaves, and circulation of exchanged ions within the plants.…”
Section: Salt Exclusion By Ultrafiltration At the Membranes Of Root Cmentioning
confidence: 99%